Shortcomings - Tomine, Adrian, 1974- (Drawn & Quarterly Pubns, 2009)
A graphic novel in which Ben Tanaka tries to salvage his failing long-term relationship with Miko Hayashi, who suspects Ben is more attracted to white women, an accusation that cause their personal and political problems to reach a boiling point.